Creative design: its preferences and evaluation - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2012)
Design is concern with the ability of a man to mould his environment to suit his material and spiritual needs. However, design preferences and evaluation are valued based judgement which may be knowledge biased, intellectual biased, authority biased or democratic biased. Therefore, this paper seeks to investigate knowledge regarding creative design preferences and how it’s being evaluated. A study was also performed to compare the design preference by authority and design preference by public opinion. This was achieved by sampling public preference among the four logos examined by a university authority. The result from the study reveals the contradiction between authority preference and the public preference.